2007
DOI: 10.1103/physrevlett.99.210601
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Time-Averaged Observables for Weak Ergodicity Breaking

Abstract: We find a general formula for the distribution of time-averaged observables for systems modeled according to the subdiffusive continuous time random walk. For Gaussian random walks coupled to a thermal bath we recover ergodicity and Boltzmann's statistics, while for the anomalous subdiffusive case a weakly nonergodic statistical mechanical framework is constructed, which is based on Lévy's generalized central limit theorem. As an example we calculate the distribution of X, the time average of the position of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
130
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 21 publications
15
130
0
Order By: Relevance
“…separation of trajectories is sub-exponential, we have a strong indication that the usual Boltzmann-Gibbs statistical mechanics is not valid. Indeed it was found that certain systems with zero Lyapunov exponents break ergodicity [8,9]. Classical entropy theory is also not applicable in this case [6,7], particularly the entropy and average algorithmic complexity grow non linearly in time [7], while for a system with a positive Lyapunov exponent they increase linearly in time.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…separation of trajectories is sub-exponential, we have a strong indication that the usual Boltzmann-Gibbs statistical mechanics is not valid. Indeed it was found that certain systems with zero Lyapunov exponents break ergodicity [8,9]. Classical entropy theory is also not applicable in this case [6,7], particularly the entropy and average algorithmic complexity grow non linearly in time [7], while for a system with a positive Lyapunov exponent they increase linearly in time.…”
mentioning
confidence: 99%
“…Its generalizations attracted vast research using different methods such as continuous time random walks [20,21] and periodic orbit theory [22] to name a few. Sojourn times of trajectories in the vicinity of the unstable fixed point are described by power law statistics leading to aging [23] and non Gaussian fluctuations [7], which are related to weak ergodicity breaking [8,9]. In the non ergodic phase z > 2 the density function of the map is concentrated on the unstable fixed point in the long time limit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ergodicity -the equivalence of the two averaging procedures-is a commonly employed assumption in statistical mechanics [1], albeit difficult to prove for realistic systems. During the past decades, the ergodicity hypothesis was intensely examined for nonrelativistic classical [2][3][4][5] and quantum models [6][7][8]. However, much less is known about its meaning and validity in relativistic settings [9], when even more basic concepts like "stationarity" may become ambigous as time becomes relative [10][11][12].…”
mentioning
confidence: 99%
“…We stress that the implementation of delays into dynamical models is sometimes tricky, as memory effects can lead to the breakdown of hypothesis that are well established for Markovian processes. In fact, there is currently a very active research on this subject from the point of view of statistical mechanics (see, for example, Allegrini et al, 2003, Allegrini et al, 2007, Rebenshtok and Barkai, 2007 and the references therein).…”
Section: Introductionmentioning
confidence: 99%